MOOCs and their Effect on the Institution: Experiences in Course Design, Delivery and Evaluation; Research; Faculty Development; Unbundling and Credits for MOOCs - Janine Kiers (FahrenHouse, 2016)
Four years after the introduction of MOOCs - which were proclaimed to be «the end of education as we know it» in 2012 - the role and effect of these free, online courses is becoming clearer. The online means of delivery to the heterogeneous audiences of MOOCs have enabled and compelled instructors and course teams to develop innovative and flexible learning materials. We can analyse the data on the study behaviour of learners to identify which course elements are effective. In addition, the integration of elements of MOOCs in campus education has resulted in promising outcomes and positive reactions from both students and teachers. On the level of the institution, we also see the effect of MOOCs: ranging from new possibilities in communication and branding, to new needs for faculty development and the support organisation. Furthermore, MOOCs play a role in the unbundling of education, e.g. the learning experience and the assessment tasks now can be uncoupled and may be delivered by different institutions and by different means: the learning experience may be in the form of a MOOC and the assessment may be a written exam at an institution.